The Detachment of Function and the Return to Essence: Exploring the Public’s Emotional Attitudes Towards Gamified Education - Liwei Ding; Hongfeng Zhang; Tuxian Zuo (Education Sciences, 2025)
Gamified education, as an emerging educational model, is gradually transforming traditional learning methods and has sparked widespread public discussion about its effectiveness and potential. According to connectivism, thinking and learning occur through the connections and interactions among a large number of units. Gamified education can serve as a form of connection, facilitating learners’ links and knowledge construction across different units through interactions, tasks, and feedback. This study aims to explore the public’s emotional attitudes toward gamified education, particularly analyzing the phenomenon of detachment and return regarding its educational function and essence. Through sentiment analysis and LDA topic modeling, three main themes were identified: the gamification and effectiveness of language learning, programmatic learning under temporal and spatial flexibility, and interactive entertainment and social learning. The study found that the public’s emotional attitude toward gamified education is diverse, reflecting the recognition of its potential in providing flexible learning and enhancing interactive experiences, as well as concerns regarding the entertainment-focused nature of educational functions. Additionally, based on the conclusions drawn, the study offers recommendations for educators and designers of gamified education to address issues such as distraction and excessive entertainment during the promotion of gamified education, helping them gain a deeper understanding of its evolution and challenges.